Faktor-Faktor yang Mempengaruhi Kadar Asam Urat pada Lansia di Puskesmas Bangetayu - Nadia Eka Pramesti; Iskim Luthfa; Moch. Aspihan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Elderly people experience physiological changes, affecting decreased kidney function, purine metabolism, and the function of the endocrine and musculoskeletal systems. This decline in body function leads to susceptibility to degenerative diseases, one of which is hyperuricemia or excess uric acid. Factors associated with gout include gender, BMI, physical activity, rest habits, and diet, as these can reduce uric acid excretion. This study was quantitative, using a retrospective cohort approach. The total sample size was 153 respondents. Sampling was conducted using the purposive sampling technique and the Slovin formula. The research instrument consisted of a dietary questionnaire, The PASE (Physical Activities Scale of Elderly) questionnaire, digital scales, metline, and the GCU Easy Touch test were used. Data were analyzed using the Spearman test and logistic regression. The results showed that the majority of respondents had a good diet, good physical activity, and a BMI of obesity category I and experienced hyperuricemia. This study showed statistical results using the Spearman test, with a value of <0.001 for diet, 0.001 for physical activity, and 0.007 for BMI. The logistic regression test showed that diet was the most influential factor with a p-value of <0.001. It can be concluded that there is a relationship between diet, physical activity, and BMI with uric acid levels in the elderly at the Bangetayu Community Health Center